Comparative Study of the Use of Doxycycline and Oxytetracycline to Treat Anaplasmosis in Fattening Lambs - Delia Lacasta; Héctor Ruiz; Aurora Ortín; Sergio Villanueva-Saz; Agustín Estrada-Peña; José María González; Juan José Ramos; Luis Miguel Ferrer; Alfredo Ángel Benito; Raquel Labanda; Carlos Malo; María Teresa Verde; et al. (Animals, 2022)
Lamb icteric carcasses condemnation due to Anaplasma ovis is causing relevant economic losses. A comparative study was developed on the effects of different antibiotics to treat ovine anaplasmosis in fattening lambs. A total of 100 A. ovis naturally infected lambs were selected and randomly divided into four groups of 25 lambs: Group ID, treated with injectable doxycycline; Group OD, oral doxycycline; Group O, injectable oxytetracycline; and Group C, untreated animals for the control group. Clinical, haematological, and molecular analyses were performed before the treatment and 12 and 45 days after the beginning of the treatments, and carcass condemnation was followed after slaughter. The A. ovis bacterial load was high before the treatments in the four groups and decreased significantly 45 days after treatment in the ID and O Groups (p < 0.001). The parameters that were related to haemolysis showed similar results. At the abattoir, 15 out of the 47 examined carcasses were condemned; 7 of C Group, 6 of OD Group, 2 of O Group, and 0 of ID Group. It can be concluded that injectable doxycycline and oxytetracycline significantly reduce A. ovis bacterial load in blood and carcass condemnation at the abattoir. Further studies are needed in order to confirm these encouraging findings.